Design and fabrication a novel probe in IR-T1 Tokamak - Ghoranneviss, Mahmood; Meshkani, Sakineh; Lafouti, Mansoureh (Вопросы атомной науки и техники, 2015)
In this paper, the first results of plasma parameters measurement by using the moveable Multi-purpose probe (MPP) have been investigated and discussed. Multi-purpose probe was designed, constructed, and installed on the IR-T1 Tokamak for the first time. This probe can simultaneously measure electric and magnetic fluctuations in three directions: poloidal, radial and toroidal. The Multi-purpose probe is composed of three sections: electrical part, magnetic part and the flow measurement section. The relation between Reynolds stress gradient and poloidal particle flux can be investigated by Multi-purpose probe. It is quite compact and does not strongly disturb plasma. In this paper, we have investigated and discussed about plasma parameters as the temporal and space evolutions of the plasma potential, Reynolds stress, poloidal particle flux, flow velocity, electrostatic fluctuations and magnetic fluctuations. The results show that the radial electric field has its maximum amount in the last Closed Flux Surface (LCFS) while poloidal electric field is minimum at this point. Also, the Reynolds stress is minimum at LCFS. The results show that decrease of the Reynolds stress cause to the remarkable increase of the poloidal particle flux. The radial electric field and poloidal flow values have been changed in the vicinity of the LCFS. This means that Reynolds stress can suppress turbulence and modify turbulence transport. Представлены и обсуждаются первые результаты, полученные с использованием подвижного многофункционального зонда (МФЗ), который был впервые установлен в камере токамака IR-T1. С помощью МФЗ можно одновременно проводить измерения флуктуаций электрического и магнитного полей в трех направлениях: полоидальном, радиальном и тороидальном. Зонд состоит из трех секций: электрической, магнитной и для измерения флуктуационных потоков. МФЗ имеет небольшие размеры и несильно возмущает плазму. С его помощью можно измерять соотношение между градиентом силы Рейнольдса и полоидальным потоком плазмы. Приводятся и обсуждаются данные о временном поведении и пространственных распределениях плазменного потенциала, силы Рейнольдса, величины полоидального плазменного потока, скорости потока, электростатических и магнитных колебаний. Из измерений следует, что вблизи крайней магнитной поверхности (LCFS) радиальное электрическое поле достигает максимума, тогда как полоидальное электрическое поле – своего минимума так же, как и сила Рейнольдса. Показано, что сила Рейнольдса вызывает существенный рост полоидального магнитного потока. Точно также в окрестности LCFS изменяются величины радиального электрического поля и полоидального потока. Из этого следует важный вывод, что сила Рейнольдса может подавлять турбулентность и обусловленный ею перенос. Представлені і обговорюються перші результати, одержані з використанням рухомого багатофункціонального зонда (БФЗ), котрий був вперше встановлено в камері токамака IR-T1. За допомогою БФЗ можна одночасно проводити вимірювання флуктуацій електричного і магнітного полів у трьох напрямах: полоідальному, радіальному и тороідальному. Зонд складається з трьох секцій: електричної, магнітної та для вимірювання флуктуаційних потоків. БФЗ має невеликі розміри, та несильно збурює плазму. За його допомогою можна виміряти співвідношення між градієнтом сили Рейнольдса та полоідальним потоком плазми. Приводяться і обговорюються дані про часову поведінку та просторові розподілення плазмового потенціалу, сили Рейнольдса, величини полоїдального плазмового потоку, швидкості потоку, електростатичних і магнітних коливань. З вимірювань виходить, що поблизу крайньої магнітної поверхні (LCFS) радіальне електричне поле досягає максимуму, тоді як полоїдальне електричне поле – свого мінімуму так, як і сила Рейнольдса. Показано, що сила Рейнольдса спричиняє істотне зростання полоідального магнітного потоку. Так саме поблизу LCFS змінюються величини радіального електричного поля та полоїдального потоку. З цього зробимо важливий висновок, що сила Рейнольдса може подавляти турбулентність і обумовлений нею перенос.